Turkish Compliance and Adaptation of EULAR 2013 Recommendations for the Management of Rheumatoid Arthritis with Synthetic and Biological Disease-Modifying Antirheumatic Drugs: Expert Opinion of TLAR - (:unkn) unknown (My University, 2015)
0

Objectives: This study aims to report Turkish League Against Rheumatism s assessment on the compliance of European League Against Rheumatism 2013 treatment recommendations for rheumatoid arthritis with practices in Turkish rheumatology clinics and adaptations for Turkey. Patients and methods: Members of Turkish League Against Rheumatism and one rheumatoid arthritis patient voted for the 2013 recommendations of the European League Against Rheumatism for treatment of rheumatoid arthritis in two sessions. An item was changed and voted again only if at least 70% of participants wanted a change. Strength of recommendations was calculated for the items. Strength of recommendations for the changed items in the first and second voting rounds was compared by Wilcoxon signed-rank test. In case of significant difference, the item with higher strength of recommendation was accepted. In case of no difference, the changed item was selected. Results: Three overarching principles and fourteen recommendations were assessed among which the three overarching principles were changed emphasizing the importance of physiatrists as well as rheumatologists for taking care of the patients. Third item was changed by adding composite indices for assessing disease activity. In the ninth recommendation, rituximab was suggested as a first line drug independent of situations like latent tuberculosis or lymphoma, etc. In the 11th recommendation, unlike European League Against Rheumatism, our committee did not suggest any thought about tofacitinib, as then it had not been approved in Turkey. Remaining principles were accepted as the same. Conclusion: Expert opinion of Turkish League Against Rheumatism for treatment of rheumatoid arthritis patients was formed for practices in Turkish clinics. Conflict of Interest The authors declared no conflicts of interest with respect to the authorship and/or publication of this article. Financial Disclosure The authors received no financial support for the research and/or authorship of this article.
Keywords: Romatoloji